2015
DOI: 10.1136/jech-2015-206278
|View full text |Cite
|
Sign up to set email alerts
|

Fish consumption and risk of depression: a meta-analysis

Abstract: This meta-analysis indicates that high-fish consumption can reduce the risk of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(120 citation statements)
references
References 35 publications
4
102
2
3
Order By: Relevance
“…A first hint of this inverse association was provided in 1998 by ecological evidence showing a lower prevalence of psychiatric disorders in countries where more (fatty) fish is being consumed, the main dietary source of fatty acids (Hibbeln 1998;Hibbeln 2002;Grosso et al 2014). Later, more detailed cross-sectional studies largely supported this ecological evidence (Grosso et al 2016;Li et al 2016). In addition, prospective studies generally also corroborated this relationship (Sanhueza et al 2013;Vermeulen et al 2016), providing further support for a possible causal relationship.…”
Section: Epidemiological Evidencementioning
confidence: 99%
“…A first hint of this inverse association was provided in 1998 by ecological evidence showing a lower prevalence of psychiatric disorders in countries where more (fatty) fish is being consumed, the main dietary source of fatty acids (Hibbeln 1998;Hibbeln 2002;Grosso et al 2014). Later, more detailed cross-sectional studies largely supported this ecological evidence (Grosso et al 2016;Li et al 2016). In addition, prospective studies generally also corroborated this relationship (Sanhueza et al 2013;Vermeulen et al 2016), providing further support for a possible causal relationship.…”
Section: Epidemiological Evidencementioning
confidence: 99%
“…29 Fish consumption may also be protective against depression according to the results of a meta-analysis of 26 epidemiologic studies. 30 The benefit of fish may be due to the greater intake of the long-chain omega-3 fatty acids since eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) may exert anti-inflammatory effects 31 and some evidence indicates that inflammation is involved in the etiology of depression, although the exact role of and mechanisms associated with inflammation remain to be determined. 32-34 Interestingly, a recent Japanese cross-sectional study found that even among a population with higher blood levels of long-chain omega-3 fatty acids, serum levels of EPA and DHA were inversely associated with depressive symptoms in community dwellers.…”
Section: Introductionmentioning
confidence: 99%
“…The association between fish consumption specifically and risk of depression was recently reviewed with results from a meta-analysis concluding that high fish consumption was associated with reduced risk of depression, the pooled risk ratio of depression for the highest versus lowest consumption of fish being 0.83 (95% CI 0.74 to 0.93) [58]. However, when studies were separated by continent, not all followed the same pattern; there were significant associations in studies conducted in Europe but not in those conducted in North America, South America, Asia and Oceania.…”
Section: Discussionmentioning
confidence: 99%